2007
DOI: 10.1021/ja077102a
|View full text |Cite
|
Sign up to set email alerts
|

DNA−Protein Cross-links between Guanine and Lysine Depend on the Mechanism of Oxidation for Formation of C5 Vs C8 Guanosine Adducts

Abstract: The reaction between N(alpha)-acetyllysine methyl ester (Lys) and 2'-deoxyguanosine (dGuo) was used to study structural aspects of DNA-protein cross-link (DPC) formation. The precise structure of DPCs depended on the nature of the oxidant and cross-linking reactions in which a series of different oxidation conditions generated a distribution of adducts, principally spirodiiminodihydantoins with lysine appended at the purine position of C5 (5-Lys-Sp), C8 (8-Lys-Sp), or both C5 and C8 (5,8-diLys-Sp). Singlet oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
182
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(190 citation statements)
references
References 77 publications
7
182
1
Order By: Relevance
“…Reactions were also conducted using cysteine as the reductant, and in order to avoid amine adducts to electrophilic dG oxidation intermediates, N-acetyl-cysteine (NAC) was used. 53,54 …”
Section: Resultsmentioning
confidence: 99%
“…Reactions were also conducted using cysteine as the reductant, and in order to avoid amine adducts to electrophilic dG oxidation intermediates, N-acetyl-cysteine (NAC) was used. 53,54 …”
Section: Resultsmentioning
confidence: 99%
“…Although there has been considerable success in the synthesis of SnO 2 nanomaterials of various morphologies [17][18][19][20], it is still a major challenge to prepare SnO 2 nanocrystals (NCs) with dimensions of less than 10 nm in different discrete sizes and relatively high BET surface area which is essential features for higher photocatalytic activity [21,22]. Furthermore, to date, many SnO 2 -based coupled semiconductor composite photocatalysts, such as SnO 2 -TiO 2 [23][24][25][26], SnO 2 -ZnO [27][28][29][30][31] or SnO 2 -CuO [32] have been extensively studied for their high photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…These adducts are likely DNA-protein crosslinks though it is currently experimentally challenging to identify these types of modifications in cells. Burrows et al showed that a crosslink between guanine base and lysine can occur when oxidized by photo-oxidants like rose bengal or riboflavin and by stoichiometric one-electron oxidants like Ir(IV) [10]. If these lesions occur in cells then their formation should be catalyzed by reactive oxygen species generated from copper or iron.…”
Section: Introductionmentioning
confidence: 99%
“…The Gh lesion is thought to form directly from the intermediate by loss of CO 2 at position six [26]. Protein-based nucleophiles have been observed to be covalently bound to DNA under oxidative conditions [10]. As a model of this complex reaction we will characterize guanine-lysine adduct formation in a nucleoside, an oligonucleotide, and a large DNA.…”
Section: Introductionmentioning
confidence: 99%